EFEKTIVITAS PENGGUNAAN MEDIA SOSIAL BAGI SISWA SEBAGAI MEDIA PEMBELAJARAN PADA MATA PELAJARAN TEMATIK INTEGRATIF DI ERA MASYARAKAT 5.0 (STUDI KASUS DI MI SALAFIYAH SIDOREJO KECAMATAN WARUNGASEM KABUPATEN BATANG) - Dalil, Akhmad (DIRASATUL IBTIDAIYAH, 2023)
AbstractThe purpose of this study was to determine the effectiveness of using social media for students as a learning medium in integrative thematic subjects in the era of society 5.0. This study uses a qualitative approach. Primary data sources in this study are class teachers and students. Secondary data sources in this study were school principals, documents, photos, school administration, class administration in MI Salafiyah, Warungasem District, Batang Regency. Data collection techniques used in this study were observation, interviews and documentation. The results of the study show that in MI Salafiyah, Warungasem District, Batang Regency, the use of social media as a learning medium in the Society 5.0 era, especially in thematic learning, is very important to be a reference for teachers today. Because the urgency and effectiveness is very visible. With several implementations of learning methods such as searching for video content about integrative thematic learning materials, watching videos given by the teacher about integrative thematic learning materials, and making videos as a form of student assignments can increase student enthusiasm for learning. By using social media as well, the level of student boredom can be reduced because it combines entertainment with learning.Keywords: Educational Game Tools, Learning Motivation, integrative thematic